Pendampingan Produksi Olahan Pangan yang Benar, Desain dan Label Kemasan Manisan Terong: Assistance in Proper Food Processing, Design and Packaging Labels for Eggplant Candy - Faridawaty, Evi; Tambunan, Ellen Christ; Kusumadati, Wijantri; Suparno, Suparno (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Challenges in MSME production include low product competitiveness, a lack of knowledge among entrepreneurs about correct production methods, and packaging and labels that are not representative, resulting in lower selling prices. Through this community service activity, it is hoped that partners will gain new knowledge and skills in proper and safe processing practices as an initial step toward encouraging compliance and obtaining legal status, as well as in label creation, packaging types, and the benefits of packaging to increase product value. The activities begin with an initial survey to identify partner needs, followed by mentoring activities comprising lectures and practical training on good food processing methods, packaging selection, and label creation assistance. The results of the activities showed an increase in the group members’ knowledge of proper processing methods and packaging label design after participating in guidance on correct processing, design, and packaging label design conducted by the community service team from the Faculty of Agriculture, Palangka Raya University.